2022
DOI: 10.1002/ptr.7629
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and synergistic antibiotic mechanism of trialdehyde phloroglucinol against methicillin‐resistant Staphylococcus aureus

Abstract: The emergence of methicillin‐resistant Staphylococcus aureus (MRSA) has become a critical global concern. Identifying new anti‐S. aureus agents or therapeutic strategies are urgently needed to treat S. aureus infection. The present study investigated the antibacterial activity of 16 phenolic compounds against MRSA, four of which exhibited antibacterial activity. Their antibacterial activities increased in a dose‐dependent manner but showed different responses with the extension of treatment time. Trialdehyde p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…The results suggested that ENT + CEO treatment was bene cial to the neutralization of negative charges on the surface of E. coli and C. albicans cells, resulting in a rapid increase of zeta potential compared with single ENT or CEO treatment. Similar synergistic effect has been reported for trialdehyde phloroglucinol combined with penicillin treatment on the zeta potential of Staphylococcus aureus (Shen et al, 2023). These effects could be mainly ascribed to the electrostatic interactions of the positively charged ENT (PI = 8.82) with negative groups such as lipopolysaccharide of the E. coli surface and phosphatidylserine of the C. albicans surface Sun et al, 2022).…”
Section: Synergistic Inhibitory Activity Of Ent and Ceo Against E Col...supporting
confidence: 77%
See 1 more Smart Citation
“…The results suggested that ENT + CEO treatment was bene cial to the neutralization of negative charges on the surface of E. coli and C. albicans cells, resulting in a rapid increase of zeta potential compared with single ENT or CEO treatment. Similar synergistic effect has been reported for trialdehyde phloroglucinol combined with penicillin treatment on the zeta potential of Staphylococcus aureus (Shen et al, 2023). These effects could be mainly ascribed to the electrostatic interactions of the positively charged ENT (PI = 8.82) with negative groups such as lipopolysaccharide of the E. coli surface and phosphatidylserine of the C. albicans surface Sun et al, 2022).…”
Section: Synergistic Inhibitory Activity Of Ent and Ceo Against E Col...supporting
confidence: 77%
“…The zeta potential is a measure of the strength of mutual repulsion or attraction between particles, which re ects the charge distribution on the surface of bacteria and fungus (Shen et al, 2023). As shown in Fig.…”
Section: Synergistic Inhibitory Activity Of Ent and Ceo Against E Col...mentioning
confidence: 99%
“…It has been reported that the strain C. freundii carries a multidrug resistance gene along with it, and is responsible for higher risk of hospital mortality 58 . S. aureus causes disease in both animals and humans and is a contaminant of food 59 . S. aureus has resistance to methicillin due to virulence gene present in it 60 .…”
Section: Resultsmentioning
confidence: 99%
“…58 S. aureus causes disease in both animals and humans and is a contaminant of food. 59 S. aureus has resistance to methicillin due to virulence gene present in it. 60 S. typhimurium causes nosocomial and food poisoning and has strong pathogenicity due to enterotoxin, endotoxin and extracellular enzymes.…”
Section: Antimicrobial Activitymentioning
confidence: 99%